Analysis Of The Principal's Role In Improving Teacher Performance And Learning Quality at SD Negeri 1 Teniga, North Lombok - Hidayati, Ismi; Hadi, Rusman; Jannah, Rauhun (International Journal of Education, Information Technology, and Others, 2025)
This study aims to determine and describe the role of the principal in improving teacher performance and learning quality at SD Negeri 1 Teniga. The method used in this research is qualitative method. The data collection tools used include three types, namely observation, structured and irregular interviews and documentation. The object of this research is the principal and teachers of grades I, IV, sports and religion teachers at SD Negeri 1 Teniga. The results of the research that have been carried out can be seen that the role of the principal in improving teacher performance and the quality of learning at SD Negeri 1 Teniga, which can show good performance, is found in four of its roles in 1) Influencing which focuses on attitude, role modeling, effective communication and policies in place. 2) Mobilizing which is reflected in the involvement of teachers and other school officials in various activities that focus on improving the quality of learning. 3) Fostering which is reflected in academic and non-academic supervision activities, providing constructive feedback. 4) Motivating which is reflected in the provision of attention, recognition, appreciation related to the needs of teachers. Teacher performance that can be improved by principals is personality, pedagogic, professional and social competencies that have an impact on improving the quality of learning that can create a positive and conducive climate in schools. However, in terms of providing school facilities such as libraries that are not available due to unsupportive school land and technological equipment such as wifi, computers are still inadequate and often experience problems, which have an impact on teacher performance and learning quality at SD Negeri 1 Teniga